2014
DOI: 10.1186/preaccept-5146409691283741
|View full text |Cite
|
Sign up to set email alerts
|

Cancer progression modeling using static sample data

Abstract: As molecular profiling data continue to accumulate, the design of integrative computational analyses that can provide insights into the dynamic aspects of cancer progression becomes feasible. Here, we present a novel computational method for the construction of cancer progression models based on the analysis of static tumor samples. We demonstrate the reliability of the method with simulated data, and describe the application to breast cancer data. Our findings support a linear, branching model for breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Several methods have been proposed to address the issue (20,21), but our numerical analysis showed that existing methods did not perform well (Supplementary Section S4). In our previous work, we conducted a proof-of-concept study that used static sample data to study cancer dynamics (22). Feature selection was performed within the framework of molecular classification by using patient survival data.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods have been proposed to address the issue (20,21), but our numerical analysis showed that existing methods did not perform well (Supplementary Section S4). In our previous work, we conducted a proof-of-concept study that used static sample data to study cancer dynamics (22). Feature selection was performed within the framework of molecular classification by using patient survival data.…”
Section: Methodsmentioning
confidence: 99%
“…However, as massive molecular profile data from excised tumor tissues (static samples) accumulates, it becomes possible to design integrative computation analyses that can approximate disease progression and provide insights into the molecular mechanisms of cancer. We have previously shown that it is indeed possible to derive evolutionary trajectories from static molecular data, and that breast cancer progression can be represented by a high-dimensional manifold with multiple branches [42].…”
Section: Learning Tree Structures From Real Datasetsmentioning
confidence: 99%
“…The dataset contains the expression levels of over 25, 000 gene transcripts obtained from 144 normal breast tissue samples and 1, 989 tumor tissue samples. By using a nonlinear regression method, a total of 359 genes were identified that may play a role in cancer development [42]. In the analysis, we set λ = 5 × N and d = 80 that retains 90% of energy.…”
Section: Learning Tree Structures From Real Datasetsmentioning
confidence: 99%
“…The desire for levels of accuracy that can ultimately lead to clinical utility continues to drive the field to refine breast cancer subtypes (Shen et al, 2013;Parker et al, 2009;Sun et al, 2017;Haibe-Kains et al, 2012;Sun et al, 2014) and to identify molecular subtypes in other cancers (Abeshouse et al, 2015;Cancer Genome Atlas Network, 2014). The recent establishment of international cancer genome consortia (Cancer Genome Atlas Network, 2012;Abeshouse et al, 2015;Cancer Genome Atlas Network, 2014;Curtis et al, 2012) has generally overcome the sample size issue.…”
Section: Introductionmentioning
confidence: 99%